Implementasi Manajemen Strategik Unit Produksi SMKN 3 Mataram - M Ary Irawan (Universitas Pendidikan Mandalika, 2018)
In order to improve the quality of education, especially in SMK, so that it can be achieved as expected, it should be supported by effective strategic management. One of the priorities that must be considered is the production unit and school services as a source of learning for students. The activities of production and service units in schools can be used as a source of learning through the planning process, production activities to marketing products in the form of goods or services. Through the activities of production and service units in schools, students are in a learning situation that is closer to the real conditions with the business or industrial world. For this reason, this study focuses more on studying the